Financial Literacy and Financial Inclusion for The Welfare of Kuningan Households: Financial Literacy and Financial Inclusion for The Welfare of Kuningan Households - Rahayu, Dwi Hartini; Nurhayati, Nurhayati; Wijaya, Richy (PENANOMICS: International Journal of Economics, 2025)
Financial literacy and financial inclusion are widely acknowledged as important determinants of household welfare, particularly in emerging economies and rural areas. This study examines the influence of financial literacy and financial inclusion on household welfare in Kuningan Regency, West Java, Indonesia. Using primary data collected from 160 households, the study applies Partial Least Squares–Structural Equation Modeling (PLS-SEM) to analyze the proposed relationships. Financial literacy is measured through financial knowledge, behavior, and attitude, while financial inclusion is assessed based on access, usage, and quality of financial services. Household welfare is captured through indicators of consumer durables, housing characteristics, and access to public utilities. The results show that financial literacy has a positive and statistically significant effect on household welfare, although its impact is relatively modest. In contrast, financial inclusion demonstrates a strong and highly significant positive influence on household welfare, indicating its dominant role in improving living standards. These findings suggest that policies aimed at improving household welfare should prioritize expanding financial inclusion while simultaneously strengthening financial literacy to ensure effective utilization of financial services.